Initial Study on the Guava Aroma of Chenin Blanc and Colombar Wines - Du Plessis, C. S.; Augustyn, O. P. H. (South African Journal of Enology and Viticulture, 2017)
An initial study indicated the importance of mercaptan on the aroma of Colombar and Chenin blanc wines. A synthesized mercaptan viz. 4-methyl-4-mercapto-pentan-2-one when added to neutral wine effected a Colombar or Chenin blanc wine aroma. The importance of sulphur components on wine aroma is emphasized.